THE EFFECTIVENESS OF THE ADIWIYATA PROGRAM IN FORMING ENVIRONMENTAL CARE BEHAVIORS IN PABANGIANG INPRES SD STUDENTS - Ashar Ashar; Nuramanah Nuramanah; Supiyati Mustari; Ramdani Ramdani (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
Study This aim for now the effectiveness of the adiwiyata program in form character care environment in students at SD Inpres Pabangiang. Approach in study This is approach qualitative, with type study studies case done _ with study field and related references _ with the topics discussed. For obtain the validity of the author's data use technique triangulation from several techniques in between observation and interview. Research results This includes: First, planning the SD Inpres adiwiyata program Pabangiang covers three aspect 1) policy school caring and cultured environment. 2) curriculum-based environment. 3) Activities based participatory It means whole inhabitant school follow participate in the adiwiyata program. With existence plan Work or group Work can increase effort enhancement performance participant learn and get role in various activity academic or non- academic. Second, the implementation of the adiwiyata program refers to four components namely 1) Development policy insightful environment. 2) Curriculum based environment. 3) Activities environment based participatory. 4) Management facilities and infrastructure friendly environment. Third, implementation adiwiyata at SD Inpres Pabangiang Already effective, because all planned activities _ in four adiwiyata programs can be implemented by all inhabitant school